Functionalized highly porous graphitic carbon fibers for high-rate supercapacitive electrodes - Wang, Huanwen (2015)
Combining high specific surface area (SSA) and superior electrical conductivity together at bulk state is very important for carbon materials in capacitive energy storage applications. Herein, by applying molten sodium metal to activate natural cotton at a relatively low processing temperature (800 °C), we have obtained hierarchically porous graphitic carbon fibers (HPGCFs) with SSA up to 1716 m2 g−1 and a high degree of graphitization in the bulk state. This is advantageous compared to amorphous carbon fibers obtained by conventional thermal annealing and KOH-activation. The obtained HPGCFs show remarkable energy storage capability (61% capacitance retention from 1 to 60 A g−1). To further increase the capacitance value, anthraquinone (AQ) molecules have been selected to functionalize HPGCFs via π–π stacking interactions. Asymmetric supercapacitors have been assembled using HPGCFs as the positive electrode and AQ-HPGCFs as the negative electrode in aqueous H2SO4 solution. The device presents a large energy density (19.3 Wh kg−1 in the applied potential range between 0 and 1.2 V) and ultrahigh power capability (up to 120 A g−1, a full charge–discharge within 0.8 s).